Safety and Effectiveness of Pharmacologic Conversion of Atrial Fibrillation and Flutter: Results of Multicenter Trial. Part I: Study Rationale, Design and Assessment of Effectiveness - N. Yu. Mironov; Yu. A. Yuricheva; V. V. Vlodzyanovskiy; S. F. Sokolov; Kh. M. Dzaurova; S. P. Golitsyn; Yu. V. Shubik; M. V. Berman; M. M. Medvedev; A. E. Rivin; D. S. Parkhomchuk; A. E. Barybin; et al. (Рациональная фармакотерапия в кардиологии)
Aim. We aimed to assess safety and effectiveness of class III antiarrhythmic drug Refralon for conversion of atrial fibrillation (AFib) and flutter (AFl) in post-registration trial and to compare data of primary center (National medical research center in cardiology) with data of other hospitals.Material and Methods. We performed retrospective cohort study in 727 patients (451 enrolled in primary center and 276 enrolled in other hospitals) admitted between June 24, 2014 and June 24, 2019. Refralon was administered for conversion of AFib and AFl in intense care units in escalating doses (10-30 mcg/kg) intravenously. Primary endpoints: restoration of sinus rhythm (SR) within 24 hours after the start of infusion of the study drug in a total dose of up to 30 pg / kg; registration of SR on an electrocardiogram (ECG) 24 hours after the start of the study drug infusion. Secondary endpoints: restoration of SR after infusion of the study drug at a dose of 10 pg / kg; restoration of SR after infusion of the studied drug in a total dose of up to 20 pg / kg; no recurrence of AFib/AFl after restoration of AFl within 24 hours of observation after the start of the study drug infusion.Results. Conversion to SR was achieved in 53,6% (391 of 727) after administration of 10 mcg/kg dose, in 73% (531 of 727) after administration of 20 mcg/kg dose and in 91,6% (666 of 727) after administration in dose up to 30 mcg/kg. SR was restored in 89% (402 of 451) of patients in primary center, and in 96% (264 of 276) of patients in other hospitals; 95% confidence interval (CI): (-0,1;-0,03). SR preserved 24 hours after conversion in 98% (650 of 666) successfully converted patients. In primary center SR preserved in 97% (390 of 402) successfully converted patients. In other hospitals - in 98,5% (260 of 264) successfully converted patients. 95 CI: (-0,09;0,06).Conclusion: In post-registration multicenter trial Refralon demonstrated high effectiveness in conversion of AFib and AFl to SR. In other hospitals Refralon did not demonstrate lower effectiveness than in primary medical center.